2017
DOI: 10.1051/swsc/2017015
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictors of eruptivity using parametric flux emergence simulations

Abstract: Solar flares and coronal mass ejections (CMEs) are among the most energetic events in the solar system, impacting the near-Earth environment. Flare productivity is empirically known to be correlated with the size and complexity of active regions. Several indicators, based on magnetic field data from active regions, have been tested for flare forecasting in recent years. None of these indicators, or combinations thereof, have yet demonstrated an unambiguous eruption or flare criterion. Furthermore, numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…These parameters (e.g., mean gradient of the horizontal magnetic field, mean current helicity, mean twist parameter, etc) are intensive (i.e., do not depend on the AR size but are spatial averages) and not extensive (i.e., dependent on the AR size and corresponding to spatial sums). Guennou et al (2017) by means of MHD analyzed a set of eruptive and non-eruptive MHD simulations and found, in agreement with Bobra and Ilonidis (2016), that intensive parameters are more relevant to eruptivity.…”
Section: Forecasting Cmessupporting
confidence: 63%
“…These parameters (e.g., mean gradient of the horizontal magnetic field, mean current helicity, mean twist parameter, etc) are intensive (i.e., do not depend on the AR size but are spatial averages) and not extensive (i.e., dependent on the AR size and corresponding to spatial sums). Guennou et al (2017) by means of MHD analyzed a set of eruptive and non-eruptive MHD simulations and found, in agreement with Bobra and Ilonidis (2016), that intensive parameters are more relevant to eruptivity.…”
Section: Forecasting Cmessupporting
confidence: 63%
“…Along with Guennou et al (2017), the present study is dedicated to the analysis of the eruptivity properties of the simulations of Leake et al (2013Leake et al ( , 2014. Our goal is to determine whether or not a unique scalar quantity, computable at a given instant, is able to properly describe the eruptive potential of the system.…”
Section: Introductionmentioning
confidence: 99%
“…related more to active-region complexity than size) physical parameters have been found to be better suited for CME prediction (Bobra and Ilonidis, 2016). Recent simulations appear to corroborate these results: for example, Guennou et al (2017) show that naturally intensive parameters related to MPILs are the most promising predictors of CMEs. Earlier studies have also shown that there may be a correlation between the CME speed and some measure of magnetic energy (Venkatakrishnan and Ravindra, 2003), reconnection flux (Qiu and Yurchyshyn, 2005), or effective connected magnetic-field strength (Georgoulis, 2008).…”
Section: Introductionmentioning
confidence: 76%